SULF2 enhances GDF15-SMAD axis to facilitate the initiation and progression of pancreatic cancer. (10th July 2022) - He, Ruizhe; Shi, Juanjuan; Xu, Dapeng; Yang, Jian; Shen, Yang; Jiang, Yong-Sheng; Tao, Lingye; Yang, Minwei; Fu, Xueliang; Yang, Jian-Yu; Liu, Dejun; Huo, Yanmiao; et al.
Abstract: Owing to the lack of early diagnosis, pancreatic ductal adenocarcinoma (PDAC) remains one of the most lethal tumours. Because acinar-to-ductal metaplasia (ADM) is a critical process to pancreatic regeneration and PDAC initiation, we applied GSE65146, a dataset composed of transcripts at different time points in wild-type and Kras G12D mutant mice upon pancreatitis induction, to obtain regeneration- and tumour initiation-related genes. By overlapping with genes differentially expressed in human PDAC, we defined the initiation- and progression-related genes, and the most prognostic gene, SULF2, was selected for further verification. By using multiple PDAC genetically engineered murine models (GEMMs), we further verified that the expression of SULF2 was increased at the ADM and PDAC stages. Functionally, SULF2 was able to promote the dedifferentiation of acinar cells as well as the metastatic ability of PDAC. Additionally, our study revealed that SULF2 could enhance TGFβ-SMAD signalling via GDF15. More importantly, serum SULF2 was elevated in patients with PDAC, and in combination with CA19-9, it provided a better method for PDAC diagnosis. Herein, our study screened out key genes for the initiation and progression of PDAC, providing potential indicators for the diagnosis of the disease. Highlights: Our research provides a new method to screen out key genes function at the initiation and progression stages of PDAC. SULF2 facilitates ADM formation and enhances proliferative and metastatic capabilities of PDAC. SULF2 promotes PDAC proliferation and metastasis via the GDF15-SMAD2/3 axis. Serum SULF2 has the potential to be developed as a biomarker to aid in the early diagnosis of PDAC.